Improving Writing Ability of the Eleventh Year Students of Man 1 Parepare by Using Dice Game - Amzah Amzah (EDUVELOP, 2017)
This research is based on two major points namely fulfilling the students’ need regards English writing ability and on how to attract the students to be active in learning process by using media. The objectives of the research are to find out whether or not the use of dice game can improve the writing ability of the eleventh year students of MAN 1Parepare and to know the use of Dice Game as learning media in improving the activeness of the eleventh year students of MAN 1Parepare in English learning process. Besides, this research is expected can be useful reference for those who want to use media in their teaching and learning process. In this research the researcher applied class action research method, with two cycles design. In one cycle consist of three meetings. The samples of the research were 17 students from Class XI IIS.2MAN 1Parepare. After analyzing the research data of students’ writing ability where the data were analyzed by using writing ability assessment from Jacob in Wiggle’s book. Meanwhile the data of students’ activeness during the studying process were analyzed by using Formula from Tiro’s book. The result of the data analysis shows the improvement of students’ writing mastery. It was showed by the mean score in cycle I (63) and in cycle II (83.18). Besides, the improvement of students’ activeness in learning English was shown by the data of observation sheet. The data of observation checklist showed that the students’ activeness in joining the learning process. From the data analysis, it is concluded that dice game can bear positive change and improvement toward students’ English writing, especially for the students of MAN 1 Parepare.